DETERMINANTS OF ZAKAT PAYMENT THROUGH DIGITAL PLATFORM AMONG MILLENNIALS AND GENERATION Z IN INDONESIA - Najhah, Alfin Nurin; Diniyah, Afrohiyatid (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study aims to analyze the factors influencing the intention to use BAZNAS’ digital platform for zakat payments among Millennials and Generation Z in Indonesia by integrating the UTAUT model with the variables of trust and the novelty variable zakat jurisprudence (fiqh zakat). Methods: This research adopts a quantitative approach by distributing questionnaires to 125 respondents and analyzing the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Results: The findings indicate that it has a direct, positive, and significant impact on the intention to use the platform. However, trust is found to be insignificant in mediating the relationship between effort expectancy, facilitating conditions, and fiqh zakat toward the intention to use. A crucial finding of this study is that trust failed to mediate the relationship between fiqh zakat and the intention to use. Conclusion and suggestion: These results emphasize the importance of building public trust in digital zakat platforms through transparency, sharia compliance, and digital education. Therefore, BAZNAS needs to strengthen its strategies regarding sharia compliance, technical aspects, and transparency to bridge the gap between muzakki's religious literacy and technological trust.